2(x+5)-6=10-x

Simple and best practice solution for 2(x+5)-6=10-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+5)-6=10-x equation:



2(x+5)-6=10-x
We move all terms to the left:
2(x+5)-6-(10-x)=0
We add all the numbers together, and all the variables
2(x+5)-(-1x+10)-6=0
We multiply parentheses
2x-(-1x+10)+10-6=0
We get rid of parentheses
2x+1x-10+10-6=0
We add all the numbers together, and all the variables
3x-6=0
We move all terms containing x to the left, all other terms to the right
3x=6
x=6/3
x=2

See similar equations:

| 3(3x-2)-2x=19+2x | | x+5/100=600000 | | 4(x-5)=6 | | X-(x•.33)=147000 | | 2−5x=9 | | 9/10k+35=-100 | | -5+12=17-3-16x | | -6(t+8)=6 | | 4x(x-1)-24=0 | | 54-19=5(x-3) | | 29-15=(x-4) | | 35+5y-4=16y-11-4y | | 0.2+w=3.6 | | 3.6+w=0.2 | | 13x^2-9x+2=0 | | 13^2-9x+2=0 | | 13x²-9x+2=0 | | 15x^2-165x-70=0 | | |3x+6|=|9x-12| | | (10-2x)*(10-2x)-(40x-4x²)=0 | | (10-2x)*(10-2x)=40x-4x² | | 4(y+7)-5=17. | | 2x-1=4x+9. | | 3.2=d-6.88 | | 2=8x-3 | | 13=4v-7 | | x/3-8=-26 | | C=80+12n | | m/5+7=11 | | 7y-8=-7+5(10y+8) | | 4x-6(3x-2)=-44 | | 10a^2+16a-26=0 |

Equations solver categories